PENGARUH TERAPI DZIKIR TERHADAP SKALA NYERI PASIEN POST OPERASI - Nurul Jannah; Muskhab Eko Riyadi (Poltekkes Kemenkes Malang, 2021)
The problem in post operative patients is the pain that is felt due to the surgical wound. After the effects of anesthesia wear off, the patient will feel pain in the area where the surgery was performed. This will cause the patient to feel uncomfortable, uneasy, restless and various other feelings or mood disorders. Physiologically, dhikr will produce several medical and psychological effects, which will balance the serotonin and norepineprine levels in the body. This is a natural morphine that works in the brain which can make the heart and mind feel calm after dhikr. This study aims to determine the effect of dhikr therapy on pain scales in post operative patients. Type of research is a pre experiment one group pretest and posttest without control. Sampling using convenience sampling technique and statistical test using paired t test. The results of the study showed that the mean pain scale before treatment was 4.95 and the mean pain scale after being given dhikr therapy was 3.90. While the significance value is 0.000 or p less than 0.05, so that there is an effect of dhikr therapy on the pain scale of postoperative patients. Nurses are expected to be able to apply dhikr therapy to patients who experience pain as an independent action by nurses in controlling pain and in reducing pain in postoperative patients.